San Juan de Dios Hospital in Arequipa: three hundred and sixty years of a ghostly story - Álvarez-Carrasco, Ricardo Iván (2020)
The purpose of this article is to reconstruct the existence of the San Juan de Dios hospital in Arequipa, which, despite its three hundred and sixty years of existence serving one of the most important cities in Peru, has been completely forgotten by its compatriots and a large part of the historians of the Peruvian medicine. This research also allows us to appreciate the administrative, normative and scientific evolution of a colonial hospital and, finally, to experience, on the front line, its final four decades, probably the most tortuous of its longexistence, in which it survived by itself and concluded in an unusual way, never seen before and after in the hospital records of the country.